Mechanical Properties of Pentagraphene-based Nanotubes: A Molecular Dynamics Study. (6th February 2018) - de Sousa, J. M.; Aguiar, A. L.; Girão, E. C.; Fonseca, Alexandre F.; Souza Filho, A. G.; Galvao, Douglas S.
ABSTRACT: The study of the mechanical properties of nanostructured systems has gained importance in theoretical and experimental research in recent years. Carbon nanotubes (CNTs) are one of the strongest nanomaterials found in nature, with Young's Modulus (EY ) in the order 1.25 TPa. One interesting question is about the possibility of generating new nanostructures with 1D symmetry and with similar and/or superior CNT properties. In this work, we present a study on the dynamical, structural, mechanical properties, fracture patterns and EY values for one class of these structures, the so-called pentagraphene nanotubes (PGNTs). These tubes are formed rolling up pentagraphene membranes (which are quasi-bidimensional structures formed by densely compacted pentagons of carbon atoms in sp 3 and sp 2 hybridized states) in the same form that CNTs are formed from rolling up graphene membranes. We carried out fully atomistic molecular dynamics simulations using the ReaxFF force field. We have considered zigzag-like and armchair-like PGNTs of different diameters. Our results show that PGNTs present EY ∼ 800 GPa with distinct elastic behavior in relation to CNTs, mainly associated with mechanical failure, chirality dependent fracture patterns and extensive structural reconstructions.